AB0939 Factors of Immunodepression in Patients with Tuberculosis in Internal Medecine. (9th June 2015) - Ben Abdelhafidh, N.; Toujani, S.; Abid, R.; Bousseta, N.; Gharsallah, I.; Othmani, S.
Abstract : Background: Immunodepressed patients are a high-risk group for tuberculosis. Objectives: The aim is to study the differences in presentation, diagnosis and therapeutic management of tuberculosis according to the immune status of patients. Methods: A retrospective study of the files of patients hospitalized in the internal department of military hospital of Tunisia for a Mycobacterium tuberculosis infection. Comparison of two populations: immunodepressed versus non immunodepressed. Results: 129 patients aged 20 to 90 were included, 49 patients were considered immunodepressed and 80 non immunodepressed. The causes of immunodepression were: age ≥65years (n=27), diabetes (n=20), immunosuppressive drugs (n=16), chronic inflammatory diseases (n=9), chronic renal failure (n=7), neoplasia (n=8), chronic hepatopathy (n=4), and HIV infection (n=2). Comparison between the 2 populations revealed a more frequent history of absence of vaccination in the immunodepressed (p=0.0001), shorter duration of hospitalisation (p=0.01), greater frequency of disseminated forms (p=0.02), more frequent use of corticoids (p=0, 007) and enhanced mortality (p=0.04). There was no difference in the 2 groups with regard to the clinical signs having evoked tuberculosis, the diagnostic method and the bacteriological results. Conclusions: The severity and the frequency of tuberculosis in immunodepressed patients should incite clinicians to evoke tuberculosis and to initiate rapidly an efficient treatment. In case of alteration in immune defenses, prophylactic treatment Disclosure of Interest: None declared